An Ethnolinguistic Study in the Names of Salt Farming Tools in Rembang District - Utama, Faris Febri; Rais, Wakit Abdullah; -, Sumarlam (Bina Nusantara University, 2019)
The aim this research was to describe the names of the tools used in salt farming in Rembang district, which was viewed from an ethnolinguistic perspective. This research was a qualitative research using the Spradley ethnographic method. Data collection used participatory observation and interview techniques. The collected data were analyzed using the ethnosains analysis model. The results show that salt farmers in Rembang regency know at least 13 names of tools in salt farming, namely: ebor, sirat, kincir, desel, garuk, kusut, slender, ekrak, tolok, mbatan, angkong, dium, and ukuran banyu. The thirteen tools can be classified according to their functions, such as (1) to move seawater; (2) to flatten the pond bottom; (3) to compact the pond bottom; (4) to move the salt into a sack or conveyance; (5) to transport the salt in storage area; (6) for coating the bottom of the pond; (7) to determine the density of seawater in the pond.